Therapy of Chronic Hepatitis C in the Era of Nanotechnology: Drug Delivery Systems and Liver Targeting - Lujan Cuestas, Maria (Mini Reviews in Medicinal Chemistry, 2017)
Since the British scientist Michael Houghton along with George Kuo, Qui-Lim Choo (Chiron Corporation Emeryville), and Daniel W. Bradley (Centers for Disease Control and Prevention) codiscovered the causative agent of hepatitis C in 1989, so much progress has been made for the screening of blood donors and management of this chronic liver disease. In this regard, direct-acting antiviral agents (DAAs) have emerged as the potential “cure” of this slowly progressing and devastating disease. However, improvements are still clearly required since the anti-hepatitis C drugs currently available in the market are so extremely expensive (i.e. 94,500 for a 12-week course of treatment), that many patients will have a denied access to such drugs by their insurers. In the last few years, nanotechnology has emerged as a new platform for drug development, contributing significantly to the improvement of the administration and delivery of many drugs. Additionally, nanotechnologies can provide unique solutions even in poorer societies. This manuscript reviews the current knowledges on the available anti-hepatitis C drugs and the new drug candidates being investigated as well, and introduces the recent advances in nanocarrier-based delivery systems. Finally, the challenges in the development of drug delivery systems for the targeting of antiviral drugs to the liver are also discussed.
Keywords: pharmacotherapy